The influence of anesthetic techniques on postoperative cognitive function in elderly patients undergoing hip fracture surgery: General vs spinal anesthesia. Issue 12 (December 2018) - Tzimas, Petros; Samara, Evangelia; Petrou, Anastasios; Korompilias, Anastasios; Chalkias, Athanasios; Papadopoulos, Georgios
Abstract: Background: Hip fracture is common and morbid in elderly patients. Postoperative cognitive dysfunction (POCD) is also very common in these subjects undergoing surgery with an incidence which exceeds 40% in some reports. To date, the evidence is ambiguous as to whether anesthetic technique may affect the patients' outcome as far as postoperative cognitive function is concerned. Objective: The aim of this study was to compare the effect of general and subarachnoid (spinal) anesthesia on the development of POCD up to 30 days after surgery in elderly patients undergoing hip fracture surgery. Methods Subjects over 65 years with hip fracture undergoing surgery were recruited for this study. They were enrolled and randomized to receive either general anesthesia (GA group) or subarachnoid (spinal) anesthesia (S group). Cognitive function was assessed using a battery of neuropsychological tests undertaken preoperatively and at 30 days postoperatively. The incidence of delirium was examined during the same period and their functional status, in terms of activities of daily living was also recorded. Results: A total of seventy patients, 33 men and 37 females, mean age of 76 years were analyzed. Thirty-three patients received general anesthesia (GA group) and 37 subarachnoid (spinal) anesthesia (S group). The two groups of patients were similar with respect to baseline characteristics, comorbidities and perioperative data. The results of neuropsychological testing showed that there were no significant differences between the groups in eight out of ten neurocognitive tests at baseline and 30 days after surgery. There was a statistically significant decline of the Instrumental Activities of Daily Living Scale score in S group compared with group GA on the 30th postoperative day (p = 0.043). A significant decline was also present in Color-Word Task test in S group compared with group GA at baseline (p = 0.014) and 30 days postoperatively (p = 0.003). Postoperative delirium was present in four patients (12%) for the GA group, and in 10 patients (27%) for the group receiving subarachnoid anesthesia. Conclusion: We concluded that the choice of anesthesia modality does not appear to influence the emergence of postoperative cognitive dysfunction in elderly patients undergoing hip fracture surgery.